La tutela entutelada: conflctividad institucional y otras dificultades polisémicas (2020)
This paper aims to make a critica! and reconstructive in nature study, scope and setbacks, the virtues and the intrinsic characteristics of guardianship action, examined from its neat and paradigmatic dimensions. It also reflects its substantive contingencies and polysemic difficulties concentrated in its essence and effe ctiveness, presenting the model of protection of the mostimportant in the history of our constitutionalism fundamental rights. Inthis fashion, it raises their significance and legal impact, hermeneutic and socio-political concentrating Guardianship at its highest expressions, thus proceeding to address and boldly present an extension of protection to the character that this mechanism offe rs and claims.